Metaplastic breast carcinoma: series of cases and literature review - Papa, Giulia; Ferreira, Carolina Fernanda; Damasio, Luisa; Prigenzi, Karla Calaça Kabbach (Mastology, 2021)
Introduction: Metaplastic breast carcinoma is a heterogeneous group of infrequent invasive carcinomas with aggressive behavior. It presents differentiation from the neoplastic ductal epithelium to squamous and/or sarcomatous mesenchymal component, through the epithelial-mesenchymal transition process, and may present morphology of epithelioid and fusiform cells, with possible cartilage, bone, lipomatous, fibromatous, smooth muscle or skeletal muscle differentiation, among others. Most of the cases present the triple-negative immunohistochemical profile. Objective: To report three cases of metaplastic carcinomas, with an emphasis on clinical and pathological aspects, in addition to conducting a literature review on this topic. Methods:The three cases were registered in the internal search system for reference services in breast pathology in São Paulo, between 2012 and 2019. For literature review, the keywords metaplastic carcinoma, breast, cancer, review, breast cancer subtype and pathological and clinical outcomes were used in PubMed. We found 154 articles, of which 42 were selected for full reading, based on the abstract and established inclusion criteria. After this initial selection, these articles were read and reviewed; nine articles that did not meet the inclusion criteria were excluded. Discussion: Three cases of metaplastic carcinoma with similar immunohistochemical characteristics have been reported. The first case is that of a 40-year-old patient with the diagnosis of metaplastic carcinoma producing a chondroid matrix with liposarcomatous and osteosarcomatous differentiation. The second case is that of a 50-year-old patient who presented with the final diagnosis for a fusocellular metaplastic carcinoma with lymph node metastasis. Finally, the third case described is that of a 59-year-old patient, who presented metaplastic carcinoma with chondroid differentiation. Conclusion: Metaplastic carcinoma is a rare and aggressive type of breast cancer, in which most of the patients have shorter survival and worse prognosis in relation to the other subtypes. More studies are needed in order to determine a gold standard treatment for this disease.